The efficacy of Tripterygium Glycosides in the treatment of Chinese patients with thyroid-associated orbitopathy: a systematic review and meta-analysis - Mingzhe Li; Bingchen Wei; Tianshu Gao; Chenghan Gao (Frontiers in Pharmacology)
ObjectiveThis study aims to conduct a systematic review of the effectiveness and safety of Tripterygium Glycosides interventions in the treatment of Chinese patients with thyroid-associated orbitopathy (TAO).MethodsA literature search was conducted using PubMed for English sources, and the CNKI, Chinese Biomedical Database, Wanfang Database, and VIP Database for Chinese sources. The search period extended from the beginning of the databases’ creation to Dec. 2023. The keywords used in the search were hyperthyroidism, thyroid-related immune orbitopathy (TRIO), ophthalmopathy, and Tripterygium Glycosides. Various combinations of search terms were used, depending on the database being queried. All the trials included in the study were clinical randomized controlled trials (RCTs).Results33 RCTs or quasi-RCTs that met the inclusion criteria were included. The meta-analysis included 27 RCTs. 6 RCTs were excluded from the analysis due to the absence of a control group, but they were still included in the systematic review. 27 RCTs or quasi-RCTs involving 2,134 patients were included in the meta-analysis. The TRIO patients in the treatment group received Tripterygium Glycosides in combination with Thiamazole, Prednisone, Levothyroxine sodium, or a combination of these medications. While the TRIO patients in the control group were treated with Thiamazole, Prednisone, Levothyroxine sodium, or a combination of these treatments, the meta-analysis results show that the overall effectiveness rate of the treatment group and the control group was P = 0.05, I2 = 0.33 < 0.5 [MD = 4.45, 95% CI (3.31, 5.99), P < 0.00001]. The former was significantly superior to the latter. At the same time, a risk assessment was conducted for the study of the 2 groups. The former was significantly superior to the latter. Furthermore, the clinical effectiveness rate of eyeball prominence was P < 0.00001, I2 = 0.98 > 0.5 [MD = 2.40, 95% CI (2.28, 2.51), P < 0.00001]. The clinical effectiveness rate of CAS score was P < 0.00001, I2 = 0.89 > 0.5 [MD = 1.68, 95% CI (1.50, 1.85), P < 0.00001]. The clinical effectiveness rate of FT3 was P < 0.00001, I2 = 0.98 > 0.5 [MD = 0.95, 95% CI (0.81, 1.08), P < 0.00001], the clinical effectiveness rate of FT4 was P < 0.00001, I2 = 0.95 > 0.5 [MD = 2.12, 95% CI (1.99, 2.25), P < 0.00001], and the clinical effectiveness rate of TSH was P < 0.00001, I2 = 0.89 > 0.5 [MD = −0.19, 95% CI (−0.21, −0.17), P < 0.00001].ConclusionThe experience with the treatment of TAO using Tripterygium Glycosides was promising. The existing evidence suggests that treatment with Tripterygium Glycosides may be more effective in enhancing the response rate, quality of life, and FT3 levels compared to treatment with Prednisone, Levothyroxine sodium, and/or Thiamazole alone.